Efforts to Improve Student Learning Outcomes Using Interactive Wordwall Media in Science Subjects for Grade 3 of SD Negeri 067240 Medan - Damanik, Elseria; Wahyuni, Sri; Lubis, Nona Alfira (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to improve the science learning outcomes of third grade students of SD Negeri 067240 Medan using Wordwall interactive media. The form of this research is classroom action research (PTK) using quantitative research using experimental methods. The results of the research found that student learning outcomes showed only 41% complete and these results were not satisfactory. Student learning outcomes in cycle I with the average score obtained was 73.5 with a student completeness rate of 65% and this is said to be quite good. Student learning outcomes in cycle II obtained an average score of 81.1 with a percentage level of completeness of 88% which can be said to be very good. From the results of the research conducted, it shows that students' science learning outcomes have improved significantly by using Wordwall interactive media.